On the age of the Nele asteroid family - Carruba, V [UNESP]; Vokrouhlicky, D.; Nesvorny, D.; Aljbaae, S. [UNESP] (Oxford Univ Press, 2018)
The Nele group, formerly known as the Iannini family, is one of the youngest asteroid families in the main belt. Previously, it has been noted that the pericentre longitudes (omega) over bar and nodal longitudes Omega of its largest member asteroids are clustered at the present time, therefore suggesting that the collisional break-up of parent body must have happened recently. Here, we verify this conclusion by detailed orbit-propagation of a synthetic Nele family and show that the current level of clustering of secular angles of the largest Nele family members requires an approximate age limit of 4.5 Myr. Additionally, we make use of an updated and largely extended Nele membership to obtain, for the first time, an age estimate of this family using the backward integration method. Convergence of the secular angles in a purely gravitational model and in a model including the non-gravitational forces caused by the Yarkovsky effect are both compatible with an age younger than 7 Myr. More accurate determination of the Nele family age would require additional data about the spin state of its members.
Keywords: minor planets, asteroids: general; minor planets, asteroids: individual: Nele; celestial mechanics